PKM MENEJEMEN MARKETING UMKM - Fajarina, Maskhurin; Nurul Laili, Elisa; Indrawan, Fani; Ertika Daristin, Pipit; Bahroodin, Ariga; Ansori, Sholihul; Anah, Lik; Amer, Afizan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Marketing is very important for entrepreneurs to attract consumers so as to increase sales results. Knowledge about branding and marketing is not easy, it is not enough just once or twice, but it needs to be done continuously. Apart from that, marketing is not just about offering to potential consumers, but requires management to maximize marketing results. Therefore, training and assistance to the public regarding marketing management, especially for novice entrepreneurs, is very important. This community service regarding